Predicting radiative properties of spacecraft body substrates - Yap, Wai Teng. (2009)
Numerous artificial satellites have been launched for the purposes of scientific, military, and commercial missions since the invention of it. Among them, micro-satellites are rapidly growing importantly in scientific and commercial realities because they provide shorter development times, smaller budgets and can achieve many of the functions of their larger counterparts – cheaper and effective. Since the thermal control subsystem is crucial for micro-satellites, viewing of reduction in space usage and mass, the passive thermal control methods are adopted.